Job resources and work engagement: the contributing role of selection, optimization, and compensation strategies at work - Matthias Weigl; Andreas Müller; Severin Hornung; Max Leidenberger; Barbara Heiden (Journal for Labour Market Research, 2014)
The life-span model of selection, optimization, and compensation (SOC) provides a valuable theoretical framework for understanding organizational behaviour related to coping with age-related changes. Although previous research has demonstrated that SOC strategies at work contribute positively to individual outcomes, the role of workplace characteristics has been insufficiently addressed. This study investigated direct and indirect effects of SOC strategies at work and two important job resources (i.e., learning and developmental opportunities and autonomy at work) in predicting work engagement. All variables were assessed through employee self-reports based on standardized survey measures. Data collected from 118 flight attendants showed that SOC strategies were positively associated with work engagement (r = 0.28, p < 0.05). Learning and developmental opportunities (r = 0.35, p < 0.01) and job control (r = 0.31, p < 0.01) were also related to work engagement. Additionally, we found meaningful mediation effects, such that positive associations of job resources with work engagement were significantly mediated through SOC use. These findings suggest that the application of successful aging strategies and enhanced job resources are conducive to engagement at work. Theoretical and practical implications regarding the joint effects of SOC strategies and job resources for successful aging in the workplace are discussed.
Keywords: 330; Lernen und Arbeiten; Arbeitsbedingungen; altersadäquate Arbeitsplätze; Flugbegleiter; ältere Arbeitnehmer; Arbeitsmotivation; Leistungsmotivation; Schweiz